Investigating Researchers ' Skills and Competency Gaps of Agriculture Student: A Needs Assessment Approach - Velamuri, Anusha; Kumar, Vinaya Kumar HM (Indian Journal of Extension Education, 2025)
The study was conducted to understand the important skills and competency gaps of student agriculture researchers for enhancing their research quality. Borich’s need assessment model was used, highlighting the needs by studying the difference between relative importance of a research skill and extent of competence. A thorough review of the literature along with experts’ advice was conducted, to collect skills needed for agriculture research, reliability was tested (Cronbach’s alpha score-0.84) and questionnaire was prepared. The obtained Mean Weighted Discrepancy Scores (MWDS) conveyed that the top three needs of student agriculture researchers were technical excellence (3.19), fund generation (2.98) and management of research activities (2.48). By attaining these skills, respondents perceive fulfilling opportunities such as publishing articles in high-rated journals (82.93%), enhancing the quality of research (78.05%) and attending national and international conferences (72.36%). Based on these results, it could be suggested that agriculture universities organize hands-on experience workshops and training sessions and encourage cross-institutional and cross-border collaborations to help improve agriculture student research activities.